Fatty acid profiling in freeze dried Avocado (Persea americana) fruit powder in FAME analysis - Jothilakshmi, Krishnan; Gayathry, Gunavijayan; Gurumeenakshi, Gurumurthy; Subramanian, Elangovan; Nirmala, Lourdhuraj (Plant Science Today, 2025)
The study explores the development and characterization of freeze-dried avocado (Persea americana) fruit powder to evaluate its potential as a functional food ingredient and its enhanced nutraceutical value. Freshly harvested avocados were procured from Gudalur, Ooty hills, Nilgiris district, Tamil Nadu, India and processed into a freeze-dried powder. Fatty Acid Methyl Ester (FAME) analysis revealed a total fat content of 44.98 %, with 31.05 % monounsaturated fatty acids (MUFA), primarily oleic acid (71 %) known for its cholesterol-lowering and heart health benefits. The powder also contained 98.70 % saturated fatty acids, 40.70 % polyunsaturated fatty acids (PUFA), trace amounts of tannins (<0.5 %) and trans fats (<0.05 %). Mineral analysis indicated significant levels of calcium (51.13 mg/100 g), magnesium (87.21 mg/100 g), potassium (1198 mg/100 g), (1.23 mg/100 g) and sodium (5.1 mg/100 g). Colorimetric analysis using the Hunter color scale demonstrated a lightness (L*) of 82.96, a greenish hue (a* = -14.32) and a yellow component (b* = 60.38) with a hue angle of 103.34º. The findings suggest that freeze-dried avocado powder retains valuable nutrients and bioactive compounds, making it a promising candidate for use in functional foods and nutraceuticals.